Pengaruh Metoda Project Based Learning (PJBL) Terhadap Hasil Belajar Siswa SMA pada Mata Pelajaran Geografi - Hilmy Fauzan Al-Hanif Adnan; Mustolikh Mustolikh (UM Purwokerto Press, 2022)
Project based learning is a learning model that uses projects or activities as a medium. Students are required to solve the problems that exist around him independently or in groups in the form of real useful products. The purpose of this study was to determine the differences in the learning outcomes of experimental class students and control classes and their effect on the learning outcomes of high school students, especially Geography subjects. Teachers or researchers have a very important role in helping to solve these problems. As an effort to improve the learning outcomes of students, one way that can be applied is the project-based learning method. At the end of the learning, it will be known whether the experimental class with the project-based learning method will be able to surpass the control class. In general, with trials and hypotheses applied, the results of the study showed a significant difference in student learning outcomes where the learning outcomes of experimental class students were higher than the control class in geography subjects. So in this case, project-based learning is very appropriate to be applied in high schools considering that Indonesia is an archipelagic country with a diverse morphology and climate accompanied by very abundant natural resources.